From the Horn of Africa to the Middle East: Human trafficking of Eritrean asylum seekers across borders - Lijnders, Laurie; Robinson, Sara (Anti-Trafficking Review, 2013)
Each month hundreds of men, women, and children flee Eritrea as a result of grave violations of human rights committed by the Eritrean government. Travelling across borders, an estimated 36,000 Eritreans have been smuggled to Israel over the past seven years. For 31 per cent of those interviewed for this research, their migration involved abduction and forced movement for extortion among other abuses. Migrants have been abducted in Eastern Sudan near the border with Eritrea and then sold to criminal gangs along the Sudan-Egypt border. The gangs forcibly hold the migrants captive in the Northern Sinai desert. Many who made the journey reported being held hostage and subjected to brutal treatment in Eastern Sudan and the Northern Sinai desert, including gang rape of men and women, whipping, and various other methods of physical and psychological torture. Although not a traditional trafficking scenario, this paper explores the phenomenon in relation to borders. Intricate trafficking networks have exploited refugee outflows from Eritrea, turning the area around the Sudanese side of the Eritrea-Sudan border into a breeding ground for abductions, aggravated smuggling, and trafficking. While crossing borders to claim asylum may facilitate some protection from abuses perpetrated by the Eritrean government, it has created a new set of challenges for Eritrean migrants who now must find protection and safety from kidnappers. While refugees must cross borders to find safety, those same borders create the circumstances for trafficking networks to operate. Unless the dynamics of those involved changes, human rights abuses such as extortion, torture and human trafficking in Eastern Sudan and Sinai are expected to continue.